2012
DOI: 10.3928/01477447-20120426-41
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Disk Herniation With Paraparesis Treated With Transthoracic Microdiskectomy in a 14-year-old Girl

Abstract: Herniated thoracic intervertebral disk causing spinal cord compression with paraparesis is uncommon in adults and rare in children. This article describes a case of pediatric thoracic disk herniation with paraparesis treated surgically.A 14-year-old girl presented with a 4-month history of diffuse back pain and sudden onset paraparesis. Motor strength was 4/5 in both legs, and she had lost the ability to ambulate. Magnetic resonance imaging revealed spinal cord compression due to a herniated intervertebral dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…This is not the case for other authors who have reported similar cases. [11][12][13][14][15][16][17][18] Apart from these few case reports, the only published results of surgery for acute myelopathy due to TDH is the series reported by Cornips et al, 8 who estimated the frequency of this condition at 4% of surgeries for TDH, highlighting the rarity of this situation.…”
Section: Discussionmentioning
confidence: 99%
“…This is not the case for other authors who have reported similar cases. [11][12][13][14][15][16][17][18] Apart from these few case reports, the only published results of surgery for acute myelopathy due to TDH is the series reported by Cornips et al, 8 who estimated the frequency of this condition at 4% of surgeries for TDH, highlighting the rarity of this situation.…”
Section: Discussionmentioning
confidence: 99%